Quadrilateral Fuzzy Number - T, Pathinathan; S, Santhoshkumar (International Journal of Engineering and Technology, 2018)
Fuzzy numbers are used to represent uncertainty. Various types of fuzzy numbers are used in practical applications. In this paper we define Perfect Pentagonal Fuzzy Number (PPFN), Quadrilateral Fuzzy Number (QNF) and Left skewed Quadrilateral Fuzzy Number and Right skewed Quadrilateral Fuzzy Number. We study their algebraic properties with numerical examples.Â Â